Effectiveness of Clinical Pharmacy Interventions in Outpatients with Type 2 Diabetes at Duc Giang General Hospital - Thi Tuyet Nhung, Tran; Minh Hang, Nguyen; Van Dan, Le; Thai Hoa, Hoang; Thu Huong, Nguyen; Thi Thuy Van, Pham; Thanh Hai, Nguyen; Thi Bich Thao, Cao (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2DO - 10.25073/2588-1132/vnumps.4762, 2025)
Objective: The study aimed to analyze the characteristics and evaluate the effectiveness of clinical pharmacy interventions in managing hypoglycemic agents for outpatients with type 2 diabetes mellitus (T2DM) in Duc Giang General Hospital. Subjects and Methods: This was an interventional study with a pre- and post-intervention assessment design. The study population included outpatients with T2DM in Duc Giang General Hospital, aged 18 years or older, with an HbA1c level ≥ 8% between April 1 st , 2024, and June 12 th , 2024, and who had been prescribed hypoglycemic agents for at least 3 consecutive months before the assessment. The clinical pharmacy interventions consisted of medication review and patient counseling on the use of hypoglycemic agents (conducted via telephone). A convenient sampling method was employed for patient recruitment. Results: A total of 536 patients underwent medication review, of whom 124 also received counseling on medication use. Drug-related problems (DRPs) in prescribing were identified in 46.3% of patients, with the most common issue being inappropriate drug selection (46.6%). A total of 221 recommendations for prescription changes were made, of which 49.8% were implemented by physicians. The prevalence of DRPs in medication use behavior was 69.4%; the DRPs related to insulin use were observed in the majority (95.1%) of patients using insulin. As a result of the intervention, the median HbA1c level decreased from 8.9% to 8.3% (p<0.001); the proportion of patients achieving the HbA1c target increased from 0.7% to 32.2%. The highest effectiveness was observed with the combined intervention of medication review and patient counseling (45.2% increase in patients achieving the target). Conclusions: Clinical pharmacy interventions significantly improved glycemic control in outpatients with T2DM. The combination of medication review and patient counseling further enhanced the effectiveness of these interventions.